Step 1

The terms in the given sequence follow the pattern: minus two, minus six, minus two, minus six, minus, and so on. Based on this pattern then

\(\displaystyle{38}-{2}={36}\)

\(\displaystyle{36}-{6}={30}\)

\(\displaystyle{30}-{2}={28}\)

\(\displaystyle{28}-{6}={22}\)

\(\displaystyle{22}-{2}={20}\)

Hence, the next number is 20.

The terms in the given sequence follow the pattern: minus two, minus six, minus two, minus six, minus, and so on. Based on this pattern then

\(\displaystyle{38}-{2}={36}\)

\(\displaystyle{36}-{6}={30}\)

\(\displaystyle{30}-{2}={28}\)

\(\displaystyle{28}-{6}={22}\)

\(\displaystyle{22}-{2}={20}\)

Hence, the next number is 20.